2018
DOI: 10.2991/ijcis.11.1.91
|View full text |Cite
|
Sign up to set email alerts
|

A Robust Predictive–Reactive Allocating Approach, Considering Random Design Change in Complex Product Design Processes

Abstract: In the highly dynamic complex product design process, task allocations recovered by reactive allocating decisions are usually subject to design changes. In this paper, a robust predictive-reactive allocating approach considering possible disruption times is proposed, so that it can absorb the disruption in the executing process and utilize the limited capacity of resource more effectively. Four indexes (Makespan, stability, robustness, and compression cost) are used to measure the quality of the proposed metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Traditionally, the execution time of tasks is determined by project managers who rely on their subjective experience, which will inevitably bring subjective limitations. e method proposed in this paper accounts for the similarity between a previous task and the current task, and it estimates the current task's execution time using the information from similar historical tasks in knowledge base [40]. e knowledge base contains the execution time, the main needed knowledge, and the satisfaction degree of knowledge for each task.…”
Section: The Efficient Task Assignmentmentioning
confidence: 99%
“…Traditionally, the execution time of tasks is determined by project managers who rely on their subjective experience, which will inevitably bring subjective limitations. e method proposed in this paper accounts for the similarity between a previous task and the current task, and it estimates the current task's execution time using the information from similar historical tasks in knowledge base [40]. e knowledge base contains the execution time, the main needed knowledge, and the satisfaction degree of knowledge for each task.…”
Section: The Efficient Task Assignmentmentioning
confidence: 99%
“…By considering the generation mechanism and the process of innovation performance in manufacturing enterprises with regard to customer preference and by referring to the existing literatures [32][33][34][35][36][37][38][39][40], in this paper we divide indicators for innovation performance in manufacturing enterprises into three categories: innovation process performance, that is, the efficiency of innovation activities; innovation output performance, that is, the effect of innovation activities; and innovation performance for customers' green preferences. In the end, the index is summed up respectively, as shown in Table 1.…”
Section: The Indicators For Innovation Performance In Enterprisementioning
confidence: 99%
“…Kolisch et al [39] proved that multi-mode resource-constrained project scheduling problem is also NP-hard. The genetic algorithm and simulated annealing algorithm have been widely used in many research fields [40]- [43], but their defects have also been found in the process of research. For example, in the early stages of the genetic algorithm, a large difference in population individuals led to premature convergence.…”
Section: Design Genetic Simulated Annealing Algorithmmentioning
confidence: 99%